Molecular identification of Calliphoridae (Diptera: Calliphoridae) of forensic importance in Colombia - Solano, Jaiber J.; Wolff, Marta; Castro, Lyda R. (Revista Colombiana de Entomología, 2013)
Recognizing the importance of the correct identification of insects associated with deceased bodies for an effective estimation of time of death, and taking into account the incidence of flies of the family Calliphoridae in corpses and the difficulty of their taxonomic determination, we evaluated the usefulness of COI mitochondrial gene sequences as a molecular diagnostic tool for identifying forensically important calliphorids in Colombia. Sequences obtained from samples collected in different regions of Colombia and other sequences taken from Genbank were used. Based on the genetic distances calculated using the K2P model, nucleotide divergence and neighbour-joining analyses were performed. Bayesian analyses were also developed and a graphical representation of the variation of the COI fragments for each species. A total 545 pb fragments were obtained; the values of intraspecific distance when all sequenced were included, ranged between 0% and 2.904% and the interspecific distance ranged between 0.188% and 18.07%, with an overlapping distance, caused mostly by the inclusion of species with only one sequence. When we excluded species with a single sequence and L. eximia was analyzed as two subgroups, a distance gap of 2.292% was obtained, which is an optimal value for the validation of this technique. Reciprocal monophyly was observed in most species. We conclude that the COI gene is a good marker for delineating species of the family Calliphoridae in Colombia.